Salvinia molesta as Zinc (Zn) Heavy Metal Phytoremediation Agents in the Water - Rosyidah, Nabila Fitri; Fida Rachmadiarti (LenteraBio : Berkala Ilmiah Biologi, 2023)
One of pollutants in waters is caused by heavy metal zinc (Zn) which comes from industrial, household, and agricultural waste, so need efforts need to reduce this waste. Phytoremediation can be solution for this problem provided that plants used have high growth rate, such as Salvinia molesta. This study aimed to determine the effect of Zn concentration on Zn absorption ability in roots and chlorophyll content. This experimental study used Randomized Block Design (RBD) design with factors Zn concentrations of 0, 2, and 4 ppm which were carried out for 14 days. Zn content in roots was tested using AAS and chlorophyll content was tested using spectrophotometer, then analyzed using one way ANOVA and Duncan. The relationship between Zn content and chlorophyll content was analyzed using Pearson Correlation. The results showed that Zn content in roots at 4 ppm Zn concentration was higher than other treatments, which was 2.40 mg/kg, while the leaf chlorophyll content was quite low, which was 9.7 µg/ml. This shows that there is effect of Zn concentration on Zn content in roots and chlorophyll content. The higher Zn concentration in planting medium, the higher Zn content absorbed by roots so that the chlorophyll content is lower.